2019
DOI: 10.1016/j.renene.2018.11.045
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid optimisation approach to improve long-term performance of enhanced geothermal system (EGS) reservoirs

Abstract: Improving the long-term performance of deep geothermal reservoirs, as an energy source, can lead to a significant increase in efficiency of heat extractions from these assets. This will assist designers, energy firms, managers, and government decision makers to plan and maintain the use of limited available energy resources and hence enhance key sustainable development goals. Enhanced geothermal reservoirs possess a multi-phase behaviour with complex interrelationship between several parameters that makes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 32 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…Fractures and fracture networks strongly affect the hydraulic and mechanical response of the underground. This is of particular relevance for geothermal technologies, which aim at producing electricity from deep geothermal resources by enhancing the permeability of a geothermal reservoir to obtain a sufficiently large heat flux on interior surfaces (Chen et al 2018;Samin et al 2019). In numerical simulations, realistic fracture networks are usually challenging to represent with a discrete geometry (i.e., a mesh), or even impossible at the macro-scale.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures and fracture networks strongly affect the hydraulic and mechanical response of the underground. This is of particular relevance for geothermal technologies, which aim at producing electricity from deep geothermal resources by enhancing the permeability of a geothermal reservoir to obtain a sufficiently large heat flux on interior surfaces (Chen et al 2018;Samin et al 2019). In numerical simulations, realistic fracture networks are usually challenging to represent with a discrete geometry (i.e., a mesh), or even impossible at the macro-scale.…”
Section: Introductionmentioning
confidence: 99%
“…While performing a parametric investigation for a multi-well reservoir, Chen and Jiang [26] found that production well configuration with respect to injection well affects the heat mining potential. Chen et al [27] used a multivariate adaptive regression spline technique coupled with hydrothermal numerical simulation to optimize the well placement under the given fault size, and permeability for a prospective geothermal site near Superstition Mountain in Southern California, USA. They found that for the maximum net profit over a period of fifty years, the optimal well spacing is 473 m at 30.7 kg/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, deep geothermal resources have not been extensively developed due to challenges in technology and economics. An enhanced geothermal system (EGS) has been proposed to extract the heat from the deep earth (Samin, et al, 2019). Previous field experiments and geothermal demonstration projects have proved the concept of EGS but, even so, most EGS projects are abandoned due to inefficient production, huge human input, and uncertain risks (Giardini, 2009).…”
mentioning
confidence: 99%
“…Previous field experiments and geothermal demonstration projects have proved the concept of EGS but, even so, most EGS projects are abandoned due to inefficient production, huge human input, and uncertain risks (Giardini, 2009). Rosemanowes geothermal project in the UK was abandoned due to a thermal breakthrough (Samin, et al, 2019). Only one EGS project, the Soultz geothermal field in France, is barely being commercially operated among more than 40 EGS projects so far (Gé rard et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation